Regional productivity and efficiency growth in Greek agriculture - Ioanna Reziti; Leonidas Zangelidis (SPOUDAI - Journal of Economics and Business, 2019)
In this paper, for the first time, we apply the Färe-Primont productivity index (FPI) to examine the agricultural total factor productivity (TFP), during the period 2004-2016, in four regions of Greece: Macedonia and Thrace (region I), Epirus, Peloponnesus and the Ionian Islands (region II), Thessaly (region III) and Central Greece, the Aegean Islands and Crete (region IV). The FPI is further decomposed into measures of technical change, technical efficiency change, scale and mix efficiency change, residual scale efficiency change and residual mix efficiency change. The results show that TFP has declined for all regions except region II. In region IV, the TFP decrease is due to the deterioration of scale and mix efficiency. In region III, the main factor for the TFP decrease is technical regression. In region I, both technical regression and the deterioration of scale and mix efficiency affect the TFP fall. Region IV experienced the highest decline in TFP mainly due to the large decrease of scale and mix efficiency. Policy implications should try to improve scale and mix efficiency by reallocating resources optimally, especially in regions I and IV. However, the need for increased investment in R&D is unquestionable as it would improve technical change.
Keywords: D24; O47; Q10; 330; Greece; Färe-Primont Index; Total Factor Productivity; Technical Efficiency; Scale and Mix Efficiency